Covalent Labeling/Mass Spectrometry of Monoclonal Antibodies with Diethylpyrocarbonate: Reaction Kinetics for Ensuring Protein Structural Integrity - Limpikirati, Patanachai K. (J Am Soc Mass Spectrom, 2020)
Diethylpyrocarbonate (DEPC)-based covalent labeling together with mass spectrometry is a promising tool for the higher-order structural analysis of antibody therapeutics. Reliable information about antibody higher-order structure can be obtained, though, only when the protein’s structural integrity is preserved during labeling. In this work, we have evaluated the applicability of DEPC reaction kinetics for ensuring the structural integrity of monoclonal antibodies (mAbs) during labeling. By monitoring the modification extent of selected proteolytic fragments as a function of DEPC concentration, we find that a common DEPC concentration can be used for different monoclonal antibodies in formulated samples without perturbing their higher-order structure. Under these labeling conditions, we find that the antibodies can accommodate up to four DEPC modifications without being structurally perturbed, indicating that multi-domain proteins can withstand more than one label, which contrasts to previously studied single-domain proteins. This more extensive labeling provides a more sensitive measure of structure, making DEPC-based covalent labeling-mass spectrometry suitable for the higher-order structural analyses of mAbs.